C-geranyl compounds from Paulownia tomentosa fruits - Smejkal, Karel; Grycová, Lenka; Marek, Radek; Lemière, Filip; Jankovská, Dagmar; Forejtníková, Hana; Vanco, Ján; Suchý, Václav (Journal of natural products, 2007)
Five geranylflavonoids, one prenylated flavonoid, and a simple flavanone were isolated from an ethanolic extract of Paulownia tomentosa fruit. Tomentodiplacol (1), 3'-O-methyl-5'-methoxydiplacol (2), 6-isopentenyl-3'-O-methyltaxifolin (3), and dihydrotricin (4) are reported from a natural source for the first time and 3'-O-methyldiplacone (6) for the first time from the genus Paulownia. The structures of the compounds were determined by mass spectrometry, including HRMS, and by 1D and 2D NMR spectroscopy. The cytotoxicity and DPPH (2,2-diphenyl-1-picrylhydrazyl)-quenching activity of some of these compounds were tested, with diplacone proving to be the best antioxidant, although the most cytotoxic compound.
Keywords: nukleární magnetická rezonance biomolekulární; Česká republika; molekulární struktura; pikráty; Molecular Structure; Czech Republic; Biphenyl Compounds; Flavonoids; Fruit; bifenylové sloučeniny; ovoce; flavonoidy; Picrates; Nuclear Magnetic Resonance, Biomolecular; Scrophulariaceae